BMW Is Powerful, Beemer Is Not: Nickname Branding Impairs Brand Performance - Zhang, Zhe; Ye, Ning; Thomson, Matthew (Journal of Marketing, 2025)
This research investigates nickname branding, a novel phenomenon whereby firms incorporate the "street" names consumers give brands into their own marketing (e.g., Bloomingdale's opening a "Bloomie's" store). While practitioners anticipate positive results from deploying this tactic, the current research serves as the first empirical investigation of its likely effectiveness. Drawing on speech act theory, the authors theorize that using a nickname in place of a formal name serves as an act of power redistribution, effectively signaling submission to consumers, thereby reducing the perception of a brand's power and weakening its performance. Through a multimethod approach that incorporates secondary data analyses, field studies, and preregistered experiments, the results support this view across a range of performance metrics. In addition, the authors show that this effect is contingent on two factors, such that nickname branding (1) harms performance more for competent brands than warm brands and (2) is less pronounced when nicknames are used in messages that are communal-oriented (vs. transactional-oriented). This research introduces a new theoretical perspective centering on the illocutionary meanings embedded in the process of naming brands and highlights actionable insights on how marketers should approach or avoid consumer-based slang in their marketing.